Indonesian Online Learning in New Normal Under Covid-19: from Traumatic to Intimacy - Darong, Hieronimus Canggung; Niman, Erna Mena (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
The purpose of this article was to provide a brief report on how online learning is seen in the context of new normal in Indonesia. By reviewing some journal articles, news reports along with some reflective experiences from students, parents, and teachers were the basis of the report in question. As such, the results and discussion were concerned with the pro and contra regarding its implementation. In this regard, the argumentations were purely from observation, news, and digital discussion with parents, students, and colleagues supported by some findings of previous research studies. Trauma, health, and practicality were the concern of the pro while facilities, personal involvement, and intimacy were the main considerations of the contra-side. Despite a growing number of research studies, online or face to face, of greater importance are teacher’s presence, cognition presence, and social presence during the process.